Validation of the gender, age, physiology model and other prognostic factors in interstitial lung disease patients with systemic autoimmune rheumatic disease - Yun Jung Hwang; Ju Kwang Lee; Jang Ho Lee; Yura Ahn; Sang Min Lee; Seokchan Hong; Ho Cheol Kim (Scientific Reports)
Abstract Patients with systemic autoimmune rheumatic diseases-interstitial lung disease (SARD-ILD) exhibit diverse clinical courses, highlighting the importance of prognostic prediction for effective management. This study aimed to validate the gender-age-physiology (GAP) model in patients with SARD-ILD and identify additional prognostic factors. Clinical data of patients diagnosed with SARD-ILD at a tertiary center in South Korea were retrospectively analyzed. Using variables from the GAP model, along with exercise capacity, chest computed tomography (CT) patterns, and clinical course factors such as progressive pulmonary fibrosis (PPF), multivariate and survival analyses were performed to evaluate prognostic factors for 3-year mortality. Among 142 patients with SARD-ILD, 27 died and one underwent lung transplantation over a median follow-up period of 32.8 months. In the multivariate analysis, higher GAP stages, the combination of radiologic usual interstitial pneumonia (UIP) patterns and exertional hypoxia during the 6-min walk test (hazard ratio [HR]: 2.506, P = 0.049), and PPF (HR 3.481, P = 0.001) were independently associated with 3-year mortality. Additionally, among patients in advanced GAP groups (GAP stage II or III, n = 45), those with both exertional hypoxia and a UIP pattern had significantly worse prognosis (median survival: 18.0 vs. 31.2 months, P = 0.042). Additional prognostic factors beyond the GAP model were identified, including exercise capacity, CT imaging patterns, and clinical course. These findings underscore the importance of incorporating multiple prognostic indicators for improved stratification and management of patients with SARD-ILD.